2003
DOI: 10.1021/jp035407f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Micro and Bulk Solvation on the Mechanism of Nucleophilic Substitution at Sulfur in Disulfides

Abstract: Computational studies of the solution-phase mechanism of nucleophilic substitution at sulfur in disulfides with explicit water representation indicate that the pathway is dependent on the substituent on the sulfur under attack. B3LYP/6-31+G* optimizations for prototype thiolate-disulfide exchange reactions were performed including one to four explicit water molecules, followed by single-point free energy calculations with B3LYP/6-31+G* and the polarized continuum model (PCM). The solution-phase mechanism is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…10 Moreover, it agrees with the mechanism of alkaline thermal decomposition of cystine or other aliphatic disulfides 41 and applies to thiolate/disulfide exchange in solution as well. [42][43][44][45] Although computer simulations have provided a rationale for the enigmatic "mechanochemical switch" discovered in experiment, there is still a crucial question open, namely if the same reaction mechanism operates in the high-force regime? In fact, there is old experimental evidence that even the traditional thermal reduction of disulfides in alkaline solution is a very complex process that is not governed by a single mechanism.…”
mentioning
confidence: 99%
“…10 Moreover, it agrees with the mechanism of alkaline thermal decomposition of cystine or other aliphatic disulfides 41 and applies to thiolate/disulfide exchange in solution as well. [42][43][44][45] Although computer simulations have provided a rationale for the enigmatic "mechanochemical switch" discovered in experiment, there is still a crucial question open, namely if the same reaction mechanism operates in the high-force regime? In fact, there is old experimental evidence that even the traditional thermal reduction of disulfides in alkaline solution is a very complex process that is not governed by a single mechanism.…”
mentioning
confidence: 99%
“…Herein, we use this strategy to measure the kinetics of thiol/disulfide exchange as a function of the restoring force of the disulfide moiety under tensile strain. Although the effect of compressive strain on the reactivity of the disulfide moiety has been extensively studied in dithiacyclopropane, ‐butane, and ‐pentane,9, 10 such is not the case for tensile strains. The known larger aliphatic cyclic disulfides are either strain‐free or their modest ring strains do not correlate with the kinetics of thiol/disulfide exchange 11.…”
Section: Methodsmentioning
confidence: 99%
“…[10,12,24] However, a common characteristic of these bridges is that they cleave easily in reduction processes. [31][32][33][34][35][36][37] In all cases, it was found that the SAS or the SeASe bond fission is the dominant process, although in the systems investigated the substituents attached to S or Se were either identical or ones of similar electronegativity. [25][26][27][28] Consequently, the most powerful techniques in protein sequencing are based on the cleavage of SAS or SeASe bridges within the protein, but the mechanisms at the molecular level are far from being well understood.…”
Section: Introductionmentioning
confidence: 92%
“…[29] Several studies have been published in an effort to characterize these bonds [30] and the intrinsic mechanisms of SAS and SeASe bond cleavage in electron attachment processes [27,28] or in nucleophilic attacks. [31][32][33][34][35][36][37] In all cases, it was found that the SAS or the SeASe bond fission is the dominant process, although in the systems investigated the substituents attached to S or Se were either identical or ones of similar electronegativity. It has been shown that when the substituents attached to the chalcogen atoms are very electronegative, cleavage of disulfide or diselenide bonds does not take place in electron attachment processes and the fission of the bond between the chalcogen and the substituent becomes the more favorable process.…”
Section: Introductionmentioning
confidence: 99%